ANALISIS KOMPARATIF PERILAKU KERJA KONTRA PRODUKTIF PADA INSTANSI PEMERINTAH DAN INSTANSI SWASTA DI BANDAR LAMPUNG - Zainnur M Rusdi (Universitas Serang Raya, 2015)
Counterproductive work culture in a variety of both private and government institutions are increasingly reducing employee productivity, so that ultimately can reduce the overall performance of the organization. Actually counterproductive work behavior is behavior that is so disturbing performance of the organization in general and decreased employee productivity in particular. The existence of counterproductive work behavior makes the performance of employees is low both in government and in private institutions.The analysis showed a significant difference between counterproductive work behavior that occurs in government agencies with counterproductive work behavior that occurs inprivate institutions, t (df = 103) = -4.360; p <0.05. overall, counterproductive work behavior have a greater tendency occurred in government agencies as compared to privateinstitutions.